Coefficient Estimates for New Subclasses of Analytic and Bi-Univalent Functions Defined by Al-Oboudi Differential Operator - Serap Bulut (Journal of Function Spaces and Applications)
We introduce and investigate two new subclasses and of analytic and bi-univalent functions in the open unit disk For functions belonging to these classes, we obtain estimates on the first two Taylor-Maclaurin coefficients and